Conversation Analysis: Turn-Taking Analysis on Najwa Shihab YouTube Channel in Collaboration With Prabowo Subianto - Jezen Bernando; Sukma, Riska Ananda; Beru Sembiring, Lina Tri Astuty (English Education Study Program Faculty of Teacher Training and Education, 2024)
The purpose of the discussion is to interpret conversation analysis, principally in the video of turn turn-taking strategy of Najwa Shihab's YouTube channel entitled “Eksklusif: Prabowo Subianto Bicara”. The researcher used the Stenstrom framework theory to consider the turn-taking strategy in communication. There are three approaches to consider the data; Start with watching the video several times. Second, identify the relevant dialogues in the video that relate to illocutionary and perlocutionary theories. At last, categorizing the dialogue in the video based on the theory of directive illocutionary and perlocutionary acts. The outcome of this research appearance that turn-taking strategies occur in communication. There are qualified starting up, prompting, interrupting, repeating words, taking over, overlapping, appealing, silent pauses, and filled pauses. The filled pause strategy is the commonplace used in the turn-taking strategy. consequently, the research advises that understanding the conversation analysis is substantial to the earnestness of people's speech. ancillary, this research is able to be worn as a consideration for the pair theoretical and practical improvement. On paper, this research encouragement the approach of conversation analysis in the strategy of turn taking.